Structural details and digital memory performances of difluorene-containing diblock copolymers in nanoscale thin films. (August 2016) - Wi, Dongwoo; Ree, Brian J.; Ahn, Byungcheol; Hsu, Jung-Ching; Kim, Jehan; Chen, Wen-Chang; Ree, Moonhor
Graphical abstract: Amphiphilic diblock copolymers bearing rigid difluorene moiety were synthesized, which revealed high thermal stability and excellent processibility. The immiscibility between the blocks induced the formation of nanostructures significantly different from those observed among common diblock copolymers. The thin film morphology parameters were investigated by synchrotron grazing incidence X-ray scattering. The morphologies were found to make influences on the electrical memory performances, in particular, the switching-ON voltage, of the polymers. Overall, the diblock copolymer films demonstrated excellent p -type unipolar permanent digital memory behaviors. Highlights: Thin film morphology details of difluorene-containing diblock copolymers were investigated. Thin film morphologies were significantly different from those observed in common block copolymers. Film morphologies caused influences on the electrical memory performances of the block copolymers. Difluorene-containing block copolymers demonstrated excellent permanent memory behaviors. Abstract: Amphiphilic poly(4-di(9, 9-dihexylfluoren-2-yl)styrene)- b -poly(2-vinylpyridine)s (PStFl2 m - b -P2VP n ) in two different compositions and their homopolymers were synthesized: PStFl211 -b- P2VP89 (50/50, volume ratio), PStFl212 -b- P2VP33 (75/25), PStFl2, and P2VP. They were thermally stable up to around 350 °C. In nanoscale thin films, the diblock copolymers exhibited various phase-separated nanostructures depending on the composition and film process condition: random two phases, horizontal hexagonal P2VP cylinders, and hexagonally-close packed (HCP) P2VP spheres. Surprisingly, the hexagonal cylinder and HCP sphere structures are quite different from those of common diblock copolymers with similar compositions. The structural details of these thin film morphologies were investigated by synchrotron grazing incidence X-ray scattering. The thin film morphologies were found to make influences on the electrical memory performances of the polymers. In particular, the switching-ON voltage was influenced by the nanostructures and the film layer thickness as well as by the composition. Overall, the diblock copolymer films demonstrated excellent p -type permanent digital memory behaviors with unipolarity, long retention time, high ON/OFF current ratio and low power consumption. These memory behaviors were governed by a trap-limited space charge limited conduction mechanism combined with ohmic conduction and a hopping process.